Minimally-invasive resection of deep-seated subcortical and intraventricular lesions using an integrated camera-port system: A retrospective case series - Robert G. Briggs; Danielle Levy; Ryan S. Chung; David J. Cote; Ishan Shah; David Gomez; Kevin Liu; James Sobieski; Jonathan Sisti; Gabriel Zada (PLoS ONE, 2026)
Minimally invasive neurosurgery using port-based systems has gained popularity over the past decade to access deep-seated lesions within the brain. These devices typically necessitate use of separate optical and illumination systems. An exception is the Aurora Surgiscope (Integra Corp.) which is a single-use, camera-port retractor with integrated lighting and visualization capabilities. We present our retrospective single-center series using this technology for the treatment of a diverse set of intra-axial lesions to demonstrate the safety and effectiveness of the device for removing deep-seated intracranial targets. A retrospective review was conducted for all adult patients who underwent removal of an intra-axial lesion using the Aurora Surgiscope camera-port from 01/11/2021–31/12/2024 at our institution. Relevant demographic, radiographic, and clinical data were collected and summarized. 25 patients were included in the series (12 females, mean age 52.4 ± 17.7 years). The camera-port system was used to treat a diverse set of pathologies, including colloid cysts (n = 6/25, 24.0%), intraparenchymal hematomas (IPH) (n = 5/25, 20.0%), brain metastases (n = 4/25, 16.0%) and ependymomas/gliomas (n = 4/25, 16.0%). Mean lesion depth was 3.5 cm. Mean lesion diameter was 3.5 cm. Median surgical time was 2.4 hours. Gross total resection was achieved in 12/17 (70.6%) operations where complete resection of the tumor or colloid cyst was the surgical objective. Four patients experienced postoperative neurologic complications, including one patient with transient short-term memory loss, two patients with transient aphasia, and one patient with persistent left-sided weakness. Median post-operative length of stay was 4 days. This case series demonstrates the feasibility of using an integrated camera-port system for the treatment of deep-seated brain lesions. The technology integrates visualization and illumination capabilities with reasonable surgical outcomes.